MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE TIPE JIGSAW PADA SISWA KELAS IV SDN 009 NONGSA TAHUN AJARAN 2018/2019 - Simanungkalit, Salohot (Jurnal Pendidikan Kreatif, 2023)
This study aims. The objectives to be achieved in research using the application of the jigsaw type cooperative learning model are as follows: (1) Knowing the application of the jigsaw cooperative learning model in learning Indonesian? (2) Knowing the use of the jigsaw type cooperative learning model in fostering student interest in learning Indonesian language? (3) Knowing that the use of the jigsaw type of cooperative learning model can improve Indonesian learning outcomes. The results showed that the use of the jigsaw type of cooperative learning model can foster interest in learning Indonesian language lessons. can be seen from the average percentage of student learning activities in each cycle. The average value of student activity in the first cycle of the first meeting was only 53.66%, increased to 69.76% at the second meeting, so that the percentage of student learning activity during the first cycle was 61.71%. Then increased in cycle II, the average percentage of student learning activity was 72.68% at meeting 1, increasing to 85.85% at meeting 2, so that the percentage of student learning activity during cycle II was 79.27%. The use of the jigsaw cooperative learning model can increase interest in learning in Indonesian lessons. This can be seen from the average value obtained in the pre-cycle is 62.82. While the average value in cycle 1 is 71.67% and increased in cycle 2 with an average value of 82.44%.